Formulation of a body scrub with pumpkin juice (curcubita moschata) and coconut pulp (cocos nucifera l.) for enhanced skin exfoliation and antioxidant protection - Fauziah Fauziah; Nawangsari Desy; Prabandari Rani; Misworo Misworo; Zakaria Nurmalia; Zarwinda Irma (BIO Web of Conferences)
This study aimed to develop a body scrub formulation combining pumpkin juice (Curcubita moschata) and coconut pulp (Cocos nucifera L.) to provide antioxidant protection, enhance exfoliation benefits, and ensure physical stability and user acceptability. Fresh pumpkin juice and dried coconut pulp were prepared as active ingredients. Four formulations with varying concentrations of coconut pulp (0%, 5%, 10%, and 15%) were combined with 20% pumpkin juice. The formulations were evaluated for physical appearance, homogeneity, pH, spreadability, emulsion type, irritation potential, and sensory qualities. All formulations were homogeneous, with pH values between 6.1 and 6.2, suitable for skin application. Spreadability ranged from 5.5 to 6.5 cm, meeting the standard criteria. No irritation was observed in any formulation. Sensory evaluations showed that the formulation with 15% coconut pulp (F3) was most preferred for its color, texture, and aroma. This study demonstrates that combining pumpkin juice and coconut pulp results in a stable, effective, and consumer acceptable body scrub formulation, with potential for commercial applications in natural cosmetics.